Design and synthesis of novel functionalized fused oxazepine and diazepine analogues containing coumarin backbone through domino reaction - Poursan, Samane; Ahadi, Somayeh; Balalaie, Saeed; Rominger, Frank; Bijanzadeh, Hamid Reza (ChemistrySelect, 2019)
A simple and straightforward approach has been developed for the synthesis of functionalized fused oxazepine and diazepine analogues containing coumarin backbone. The approach was done through three-component reaction of 4-chloro-3-formylcoumarin, triphenyl-λ5-phosphanylidene derivatives and 2-aminophenol or o-phenylenediamine derivatives in the presence of cesium carbonate at room temperature. Carrying out the same reaction without base led to 4-aminoarylcoumarins. Mild reaction conditions and synthesis of fused functionalized heterocyclic backbones are advantages of this approach.
Gesehen am 22.10.2019